METAPROGRAM APPROACH IN THE PROCESS OF SELECTION AND ASSESSMENT OF PERSONNEL IN FINANCIAL INSTITUTION - Kochuma, I.; Lakutin, D. (Socio-economic relations in the digital society, 2021)
The aim of the article is to deepen the theoretical foundations and develop practical recommendations for the use of meta-program approach in the selection and evaluation of personnel in domestic financial institutions. The article summarizes various approaches to the definition of «metaprogram» in the field of personnel management and proposes its own definition of this category; the place and value of metaprograms in the job profile are determined; a standard metaprogram profile of the position of a financial institution risk management specialist is proposed and recommendations are provided for building a competency interview and interpreting its results in order to identify relevant metaprograms of an employee or candidate for this position. It has been proven that the main condition for successful detection of metaprograms in the interview processis the use of the right questions and the correct interpretation of answers to them, which helps to identify stable deep psychological attitudes that determine human perception of objective reality and response to organizational methods. Metaprograms are a kind of filter of information coming from objective reality to human consciousness through the senses, turning it into subjective perception and the corresponding reactions associated with it. The use of a metaprogram approach in assessing a person’s suitability for the position, along with classical, traditional methods, avoids errors in the selection and evaluation of staff. Defining and taking into account employee metaprograms is also the key to more effective management. In addition, it allows him to find a job in which he will be most effective, and the activity itself, in accordance with the internal attitudes of the employee, will bring him maximum pleasure. Taking into account metaprograms allows you to use adequate tools to stimulate work, gives an understanding of the causes of certain interpersonal relationships in the team, helps prevent conflicts and high staff turnover.Keywords: metaprogram, human resources management, personnel, financial institution, job profile.JEL Classification M12, M51, G21Formulas: 0; fig.: 1; tabl.: 1; bibl.: 16.
Keywords: metaprogram; human resources management; personnel; financial institution; job profile